A Prospective, Observational Study to Assess the Effectiveness of Enhanced Recovery After Surgery (ERAS) Protocol in Patients Undergoing Colorectal Surgery - Kevin Alfred Samuel; Shankar Gururaj Kollampare; Rakesh A Rai (Journal of Medical Sciences and Health)
Objective: To assess the effectiveness of Enhanced Recovery After Surgery (ERAS) protocol in patients undergoing colorectal surgery in reducing the length of hospital stay by early initiation of oral feeds and early mobilization. Methods: A total of 100 patients undergoing colorectal surgeries above 18 years of age for a period of 2 years i.e. from 2018- 2020 were included in the study after obtaining informed consent at a tertiary care medical college hospital. We compared the benefits of ERAS protocol in colorectal surgeries by dividing the study population as ERAS group and controlled group and were assessed using a structured proforma, parameters like type of surgery done, early initiation of mobilization, incentive spirometry and initiation of feeds were all assessed between the two groups. Results: the study population was divided into 2 group of 50 each, all the ERAS group of patients were mobilized on post operative day (POD) 1 or 2 irrespective of the surgery done and the mean duration was 1.2 days +/- 0.5 days and initiated with incentive spirometry from POD 1 with the mean duration being 1.02+/- 0.1 and the patients with laparoscopic surgery had a reduced pain and early recovery time and thus reduced the length of hospital stay in the ERAS group 5-8 days when compared to the control group 10-11 days. Conclusion: ERAS is a well-designed protocol and had a positive impact on its application in patients undergoing laparoscopic colorectal surgery in terms of decreasing the length of hospital stay.